Marxist Perspective on Health and Health Education: Critically Review in Nepalese Context - Thapaliya, Samjhana (Chaturbhujeshwar Academic Journal, 2023)
The application of Marxist philosophy in the realm of health and health education offers a critical lens through which to understand the intricate relationship between socioeconomic structures, power dynamics, and individuals' well-being. Grounded in the principles of dialectical materialism and historical materialism, Marxist thought underscores the impact of class struggle, capitalism, and exploitation on the healthcare system and the dissemination of health education. The aim of this paper is to use Marxism to analyze health and health education, emphasizing its implications for addressing systemic inequalities and advancing a more equitable approach to healthcare. In this review, Marxist philosophy has been explained based on the literature reviews available in peer-reviewed academic articles and books. By interrogating the root causes of health disparities and advocating for structural change, this perspective holds the potential to reshape healthcare systems and education paradigms, fostering a more just and equitable approach to health for all in Nepal.